EFFECTS OF GLYCEMIC VARIABILITY ON THE PROGRESSION OF DIABETIC RETINOPATHY AMONG PATIENTS WITH TYPE 2 DIABETES. Issue 7 (July 2021) - Park, Jae Yong; Hwang, Je Hyung; Kang, Min Ji; Sim, Ha Eun; Kim, Jae Suk; Ko, Kyung Soo
Abstract : Purpose: To evaluate the effects of glycemic variability on the progression of diabetic retinopathy (DR) among individuals with Type 2 diabetes and to test the hypothesis that consistent glycemic control delays the progression of DR. Methods: This retrospective study included 1, 125 participants with a follow-up period of more than 5 years and more than 20 glucose laboratory test results. The hazard ratio of ≥3 steps of progression on the Early Treatment Diabetic Retinopathy Study person scale and progression to proliferative DR were assessed. Results: An increase in the HbA1c SD was associated with a higher risk of ≥3 step progression ( P < 0.001) and progression to proliferative DR ( P < 0.001). Not only mean HbA1c, but also HbA1c SD was associated with a lower risk of ≥3 steps of progression ( P < 0.001), and progression to proliferative DR ( P < 0.001). Conclusion: Achievable and consistent glycemic control may contribute to the delay in DR progression. Clinical Trial Registration Number: Institutional review board of Inje University (No. 202003014). Abstract : Not only mean HbA1c, but also HbA1c SD was associated with a lower risk of ≥3 steps of progression, and progression to proliferative diabetic retinopathy. Achievable and consistent glycemic control may contribute to the delay in diabetic retinopathy progression.